An applied process for airline strategic fare optimization. Issue 5 (October 2016) - Ratliff, Richard; Vinod, Ben
Abstract Sabre has developed a new decision support prototype for proactive pricing and price leadership to help airlines achieve their overall marketing objectives. The strategic pricing business process described in this article is recognized as important and introduces a new paradigm for establishing fare levels for airline pricing departments. Our proposed approach is analogous to revenue opportunity modeling but applied to airline pricing. It involves perfect hindsight review of price and sales information from prior seasons and applying methods such as price elasticity, game theory and optimization models to estimate the price-level changes needed to further improve revenue, share or yields. By knowing the direction and magnitude of recommended changes in previous seasons, these hindsight review tools help pricing managers make better price-setting decisions for future seasons.